EFFECTS OF A MOOD INDUCTION PROCEDURE IN SELF-EFFICACY - Rey, Marta; Blasco, Tomás; Borràs, F. Xavier (Anales de Psicología / Annals of Psychology, 2000)
In order to test the assumption that positive and negative mood states influence the self-efficacy related to hypothetical situations and not the self-efficacy related to specific tasks which are well-known by the subject, an experiment with 57 volunteer females was developed. Subjects were randomly assigned to a positive mood or to a negative mood induction procedure by viewing films with emotional contents. Self-efficacy about specific tasks and hypothetical situations was assessed before and after this induction. Results show that self-efficacy about specific tasks is not affected by mood and that a negative mood state makes unlikely to achieve a high level of self-efficacy about hypothetical situations.